Obesity-related renal dysfunction: gender-specific influence of visceral adiposity and early impact of metabolic and bariatric surgery - Popa, Miruna Maria; Sirbu, Anca Elena; Malinici, Elisabeta Andreea; Copaescu, Catalin; Fica, Simona (Frontiers in Endocrinology, 2024)
Renal dysfunction is a recognized complication of obesity with an incompletely characterized pathophysiology. Improvement of glomerular filtration rate (GFR) after metabolic and bariatric surgery (MBS) has been reported across all classes of renal function. Inter-gender differences with regard to correlates of renal function have been described, but the influence of body composition is an understudied area. We aimed to explore determinants of renal function in obesity and to assess its variations after MBS, with a focus on body composition parameters in males and females, respectively. Materials, methods: We conducted a retrospective study on 196 patients who underwent laparoscopic sleeve gastrectomy, evaluated preoperatively and 6 months after the intervention. Recorded data included clinical and biochemical assessment, as well as body composition estimation via dual-energy X-ray absorptiometry. Serum creatinine-based formulas were used for the estimation of GFR. Results: We included a total of 196 patients (80 males and 116 females), with a mean age of 41.43 ± 10.79. Mean baseline body mass index was 42.6 (6.61) kg/m 2 and 6 months excess weight loss (EWL) reached 71.43 ± 17.18%, in females, estimated GFR correlated negatively with visceral adipose tissue (VAT) mass (rho=-.368) and this correlation was stronger in females with type 2 diabetes mellitus. Moreover, women in the third VAT mass tertile were 5 times more likely to have reduced GFR compared to the first tertile. Renal function improved after MBS across all classes of filtration. In males, this improvement correlated with EWL (rho=.358) and lean mass variation (rho=-.412), while in females it correlated with VAT mass variation (rho=-.266). Conclusions: Our results are consistent with previous findings on the positive impact of MBS on renal function and suggest a more prominent impact of visceral adiposity on GFR in females. * values are expressed either as mean ± SD, or as median (interquartile range), depending on the type of distribution BMI = body mass index, EWL = excess weight loss, eGFR = estimated glomerular filtration rate (determined by CKD-EPI 2021 creatininebased formula), VAT = visceral adipose tissue, ASMI = appendicular skeletal muscle index